Estructura de empresa y adopción de tecnología: Conservación de suelos - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2004)
– Continued growth of agricultural output requires maintenance of the productive capacity of land through time. This paper analizes the linkages between firm size, land tenure and adoption of a soil conservation practice (no-tillage technology). Representative microeconomic data of the principal agricultural area of Argentina is used. The paper tests several hypothesis relative to determinants of adoption of conservation technology. Results show that adoption of this technology is positively related to firm size. Further, owner-renters show adoption levels that are higher than those for pure owners. The paper argues that soil conservation perspectives are currently more favorable than the ones prevalent 2 or 3 decades ago, notwithstanding the important increase in land-use intensity that has occured since then.
Keywords: Q15; Q24; 330; Landwirtschaftliches Betriebssystem; Betriebsgröße; Bodenrecht; Bodenschutz; Agrartechnik; Argentinien